Digital distraction vs. frozen relief: Battling pain and anxiety in type 2 diabetes, a randomized controlled trial - Aktura, Seher Cevik; Saritas, Seyhan Citlik (Elsevier, 2025)
Objective: This study aims to examine the effects of virtual reality and ice application on pain and anxiety levels in patients with Type 2 diabetes. Methods: This study was conducted as a randomized controlled clinical trial. The sample of the study consisted of 159 patients with Type 2 Diabetes in two experimental (virtual reality and ice group) and one control group (53 patients in each group). Participant Introduction Form, State Anxiety Scale and Visual Analogue Scale were used to collect the data. Results: The findings of this study showed that the patients in the virtual reality and ice group had significantly lower post-application pain levels, compared to the control group (p < 0.001). Also, the anxiety levels of the virtual reality group participants were found significantly lower than the ice and control group (p < 0.001). Conclusions: As a result of the study, it was found that the use of virtual reality reduced anxiety and pain levels, while the use of ice reduced pain levels.
Keywords: Anxiety; Ice application; Pain; Type 2 diabetes; Virtual reality